ASPEK HUKUM PENGGUNA JASA TRANSPORTASI UDARA KOMERSIL - Nurlely Darwis (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2017)
As an archipelago, Indonesia definitely need transportation services in order to connect the islands one and other, and also between countries. The high rate of consumers has indicated the opportunities of transportation services as a lucrative business. Air transport Enterprises for the mobility of people and goods within and between the countries play role as an encourage and driven instruments of regional growth and developments. Therefore it is necessary to have the clear regulation of rights and responsibilies of the carrier. There should also other special regulations to ensure legal protection for air passengers as has been stated in the Act 8 of Consumer Protection 1991, and the Act 1of Aviation 2009.